Incestuous - El Hajj, Sleiman (2022)
Childhood sexual abuse, including incest, is underreported and often unreported in the staunchly patriarchal Lebanese setting. The revolutionary spirit that accompanied the country’s October 2019 uprising instigated hope that Lebanese patriarchy, and its concomitant juggernaut of warlords and/or formidable father figures—social, political, cultural, religious, and familial—were not immune to opprobrium in public and private spheres alike. It is within this context that this poem’s protagonist, a friend and fellow demonstrator, managed to share her memories of traumas lived in 1980s Beirut. Written not only with the permission but also at the request of the subject in the story, this childhood memory in verse retells its female narrator’s experiences of child sex abuse in Lebanon, a topic largely shrouded in debilitating silence.